Strengthening Business Management and Digital Marketing for the Cagcag Sari Bhakti Weaving SME in Banjar Pesalakan, Pejeng Kangin, Tampaksiring, Gianyar - Pulawan, I Made; Sara, I Made; Widari, Dewa Ayu Niti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Bali is renowned worldwide for its culture, including traditional woven fabric (tenun). Despite the influx of modern fabrics, many locals are determined to preserve traditional fabrics like Cagcag weaving from Banjar Pesalakan, Pejeng Kangin Village. Demand for these traditional woven fabrics has increased, overwhelming artisans due to the slow, manual production process. The community service activities target is Cagcag Sari Bhakti Weaving Group. According to Mr. Made, the group faces business development challenges, limited management skills, and a lack of accounting knowledge. They also underutilize digital marketing. The partnership program aims to boost sales and improve financial records through financial management assistance, production management guidance, and digital marketing education. The program has enhanced book-keeping, business management efficiency, and market reach.Bali is renowned worldwide for its culture, including traditional woven fabric (tenun). Despite the influx of modern fabrics, many locals are determined to preserve traditional fabrics like Cagcag weaving from Banjar Pesalakan, Pejeng Kangin Village. Demand for these traditional woven fabrics has increased, overwhelming artisans due to the slow, manual production process. The community service activities target is Cagcag Sari Bhakti Weaving Group. According to Mr. Made, the group faces business development challenges, limited management skills, and a lack of accounting knowledge. They also underutilize digital marketing. The partnership program aims to boost sales and improve financial records through financial management assistance, production management guidance, and digital marketing education. The program has enhanced book-keeping, business management efficiency, and market reach.Bali is renowned worldwide for its culture, including traditional woven fabric (tenun). Despite the influx of modern fabrics, many locals are determined to preserve traditional fabrics like Cagcag weaving from Banjar Pesalakan, Pejeng Kangin Village. Demand for these traditional woven fabrics has increased, overwhelming artisans due to the slow, manual production process. The community service activities target is Cagcag Sari Bhakti Weaving Group. According to Mr. Made, the group faces business development challenges, limited management skills, and a lack of accounting knowledge. They also underutilize digital marketing. The partnership program aims to boost sales and improve financial records through financial management assistance, production management guidance, and digital marketing education. The program has enhanced book-keeping, business management efficiency, and market reach